MAKNA TEOLOGIS YESUS “MELEWATI” SEBAGAI RESPONS GEREJA BAGI #INDONESIAGELAP – KONTEKSTUALISASI MARKUS 6:45-52 MENGGUNAKAN MODEL BUDAYA TANDINGAN - Ronny (THEOSOPHIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract The hashtag “Dark Indonesia” (or “Indonesia C[E]mas” as an irony of “Indonesia Emas”) has become very popular as a representation of anxiety on social media because of the political, economic, social and cultural context that is considered to be heading towards decline or deterioration in our country. The people of God, as part of this country, must certainly be part of the solution. But what is the truth of the Gospel as a reflection and basis for taking action? This article explores the word “passing” in Mark 6:45-52 and two passages of the Bible in the Old Testament to bring out the original meaning and message of God's word for His people in the midst of the problematic situations and conditions in general in Indonesia today. This article does not aim to produce practical and final solutions to all or one of the problems in a particular field, but by using the contextual theology model of Stephen Bevans' Counterculture, this article attempts to produce a contextual theological message that is expected to be a means by the Holy Spirit to provide comfort, perseverance and illumination for readers of this article and apply the message and contribute to our country. The exploration of theological messages is carried out through a literature study approach with primary sources from the Bible text regarding the word "passing through" and contextualized through the Counterculture model. The word “passing” has a strong theological meaning and empowers God's people in the midst of problematic situations, where based on the results of the study, the motif of “passing” in the Bible states the epiphany of God in and through Jesus Christ which has implications for His people who gain strength from this motif by realizing that God continues to reveal Himself through the actions of His people in the midst of struggles or crises in the context of Dark Indonesia. Abstrak Tagar “Indonesia Gelap” (atau “Indonesia C[E]mas” sebagai ironi dari “Indonesia Emas”) menjadi sangat populer sebagai representasi kegelisahan di media sosial karena konteks politik, ekonomi, sosial dan budaya yang dianggap menuju kemunduran atau kemerosotan di negeri kita. Umat Allah, sebagai bagian dari negeri ini tentu harus menjadi bagian dari solusi. Namun, apa kebenaran Injil sebagai refleksi dan dasar untuk melakukan tindakan? Tulisan ini mengeksplorasi kata "melewati" dalam Markus 6:45-52 dan dua bagian Alkitab di Perjanjian Lama untuk membawa keluar makna asli dan pesan firman Tuhan bagi umat-Nya di tengah situasi dan kondisi problematik secara umum di Indonesia saat ini. Tulisan ini tidak bertujuan menghasilkan solusi praktis dan final terhadap semua atau salah satu problem pada bidang tertentu, melainkan dengan menggunakan model teologi kontekstual Budaya Tandingan dari Stephen Bevans, tulisan ini berupaya untuk menghasilkan pesan teologi kontekstual yang diharapkan menjadi sarana oleh Roh Kudus untuk memberi penghiburan, ketekunan dan iluminasi bagi pembaca tulisan ini dan menerapkan pesan serta berkontribusi bagi negara kita. Eksplorasi pesan teologis dilakukan melalui pendekatan kajian studi literatur dengan sumber primer dari teks Alkitab mengenai kata “melewati” dan dikontekstualisasikan melalui model Budaya Tandingan. Kata “melewati” memiliki makna teologis yang kuat dan memberdayakan umat Allah di tengah-tengah situasi problematik, di mana berdasar hasil penelitian, motif "melewati" dalam Alkitab menyatakan epifani Allah di dalam dan melalui Yesus Kristus yang yang membawa implikasi bagi umat-Nya yang memperoleh kekuatan dari motif ini dengan menyadari bahwa Allah terus menyatakan diri-Nya melalui tindakan umat-Nya di tengah pergumulan atau krisis dalam konteks Indonesia Gelap.